Continued Alcohol Misuse in Human Cirrhosis is Associated with an Impaired Gut–Liver Axis. (11th October 2017) - Bajaj, Jasmohan S.; Kakiyama, Genta; Zhao, Derrick; Takei, Hajime; Fagan, Andrew; Hylemon, Phillip; Zhou, Huiping; Pandak, William M.; Nittono, Hiroshi; Fiehn, Oliver; Salzman, Nita; Holtz, Mary; et al.
Abstract : Background: Cirrhosis and alcohol can independently affect the gut–liver axis with systemic inflammation. However, their concurrent impact in humans is unclear. Methods: Our aim was to determine the effect of continued alcohol misuse on the gut‐liver axis in cirrhotic patients. Age‐ and MELD‐balanced cirrhotic patients who were currently drinking (Alc) or abstinent (NAlc) and healthy controls underwent serum and stool collection. A subset underwent upper endoscopy and colonoscopy for biopsies and duodenal fluid collection. The groups were compared regarding (i) inflammation/intestinal barrier : systemic tumor necrosis factor levels, intestinal inflammatory cytokine (duodenum, ileum, sigmoid), and ileal antimicrobial peptide expression; (ii) microbiota composition : 16SrRNA sequencing of duodenal, ileal, and colonic mucosal and fecal microbiota; and (iii) microbial functionality : duodenal fluid and fecal bile acid (BA) profile (conjugation and dehydroxylation status), intestinal BA transporter (ASBT, FXR, FGF‐19, SHP) expression, and stool metabolomics using gas chromatography/mass spectrometry. Results: Alc patients demonstrated a significant duodenal, ileal, and colonic mucosal and fecal dysbiosis, compared to NAlc and controls with lower autochthonous bacterial taxa. BA profile skewed toward a potentially toxic profile (higher secondary and glycine‐conjugated BAs) in duodenal fluid and stool in Alc patients. Duodenal fluid demonstrated conjugated secondary BAs only in the Alc group. There was a greater expression of all ileal BA transporters in Alc patients. This group also showed higher endotoxemia, systemic and ileal inflammatory expression, and lower amino acid and bioenergetic‐associated metabolites, without change in antimicrobial peptide expression. Conclusions: Despite cirrhosis, continued alcohol misuse predisposes patients to widespread dysbiosis with alterations in microbial functionality such as a toxic BA profile, which can lead to intestinal and systemic inflammation. Abstract : In patients with cirrhosis who continue to misuse alcohol, there is evidence of greater endotoxemia and systemic inflammation stemming from widespread intestinal mucosal dysbiosis and microbial functionality. This is perpetuated by an altered enterohepatic cycling of bile acids and overproduction of secondary bile acids in the setting of ileal inflammation.